2014
DOI: 10.1038/ncomms6190
|View full text |Cite
|
Sign up to set email alerts
|

Integrated control of hepatic lipogenesis versus glucose production requires FoxO transcription factors

Abstract: Insulin integrates hepatic glucose and lipid metabolism, directing nutrients to storage as glycogen and triglyceride. In type 2 diabetes, levels of the former are low and the latter are exaggerated, posing a pathophysiologic and therapeutic conundrum. A branching model of insulin signaling, with FoxO1 presiding over glucose production and Srebp–1c regulating lipogenesis, provides a potential explanation. Here we illustrate an alternative mechanism that integrates glucose production and lipogenesis under the un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

32
171
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 164 publications
(203 citation statements)
references
References 48 publications
32
171
0
Order By: Relevance
“…We measured liver fat and glycogen content and found no difference between the groups in either; we did find liver fat content was positively associated with liver glycogen content. Animal studies have suggested in insulin resistance, portal hyperinsulinemia drives FoxO inactivation, leading to a decrease in the hepatic glucose 6-phosphatase catalytic subunit-to-glucokinase ratio and increased hepatic DNL, TG, diacylglycerol, and glycogen content (32). Our findings of higher hepatic DNL in HI compared with NI individuals are in line with this concept.…”
Section: Discussionsupporting
confidence: 81%
“…We measured liver fat and glycogen content and found no difference between the groups in either; we did find liver fat content was positively associated with liver glycogen content. Animal studies have suggested in insulin resistance, portal hyperinsulinemia drives FoxO inactivation, leading to a decrease in the hepatic glucose 6-phosphatase catalytic subunit-to-glucokinase ratio and increased hepatic DNL, TG, diacylglycerol, and glycogen content (32). Our findings of higher hepatic DNL in HI compared with NI individuals are in line with this concept.…”
Section: Discussionsupporting
confidence: 81%
“…In addition to maintaining robust expression of ␤-cell identity factors, FoxO1 appears to regulate the balance of glucose versus lipid utilization in islets as it does in liver (37). The key finding of the present study is the decrease of lipid utilization by purified islets in the presence of elevated glucose.…”
Section: Discussionsupporting
confidence: 49%
“…Previous studies indicate that FOXO1 overexpression in the liver increased hepatic triacylglycerol content, owing to increased triacylglycerol synthesis [40,41], while recent studies suggest that FOXO proteins suppress hepatic lipogenesis and triacylglycerol levels [42,43]. In this study we show that overexpression of FOXQ1 decreases hepatic and serum triacylglycerol contents in db/db and DIO mice.…”
Section: Discussionsupporting
confidence: 45%